2007
DOI: 10.1007/s10551-007-9629-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethical Orientation and Professional Commitment on Earnings Management Behavior

Abstract: earnings management behavior, professional commitment, ethical orientation, decision-making, structural equation modeling,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
3
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 34 publications
6
88
3
16
Order By: Relevance
“…They found that practitioners' ethical judgements and self-reported behavioural intensions were primarily affected by the moral equity and contractualism dimensions of the MES while failing to observe a consistent relationship between the utilitarianism dimension and either ethical judgements or behavioural intentions. 3 A study by Greenfield et al (2007) also considers how the ethical orientation of tax practitioners in terms of idealism and relativism affects professional commitment.…”
Section: Prior Studies On Tax Practitioners and Ethicsmentioning
confidence: 99%
“…They found that practitioners' ethical judgements and self-reported behavioural intensions were primarily affected by the moral equity and contractualism dimensions of the MES while failing to observe a consistent relationship between the utilitarianism dimension and either ethical judgements or behavioural intentions. 3 A study by Greenfield et al (2007) also considers how the ethical orientation of tax practitioners in terms of idealism and relativism affects professional commitment.…”
Section: Prior Studies On Tax Practitioners and Ethicsmentioning
confidence: 99%
“…En cambio, las evidencias encontradas en torno a los factores adquiridos sí que parecen ser más concretas. De hecho, puede afirmarse que los factores relacionados con la personalidad mantienen relación con el comportamiento ético del individuo (Hegarty y Sims, 1978Hollon y Ulrich, 1979;Singhapakdi, 1993;Rallapalli et al, 1994;Rayburn y Rayburn, 1996;Fritzsche y Oz, 2007;Greenfield et al, 2008;Schneider et al, 2010) y que tanto el tipo de empleo previo como el número de años trabajados no son determinantes ni de las creencias éticas ni de la toma de decisiones (Kidwell et al, 1987;Callan, 1992).…”
Section: Relaciones Factores-prácticas-efectosunclassified
“…As an important factors determining people's work behavior, the topic of PC has been attracting many researchers' attention, e.g., Dwivedula and Bredillet (2010), Teng, et al (2009), Chen, et al (2008, Greenfield, Norman and Wier (2008), McComb (2006), Wang and Armstrong (2004), Lee, Carswell and Allen (2000), Hoff (2000), Dwyer, Welker and Friedberg (2000), Irving, Coleman and Cooper (1997), and Meyer, Allen and Smith (1993). Previous studies have contributed to the literature such aspects as measurements of PC, relationships between PC and organizational commitment (OC), and relationships between PC and its antecedent or consequence variables.…”
Section: Measuring Professional Commitmentmentioning
confidence: 99%
“…They just substitute the word 'profession' for 'organization'. Greenfield, Norman and Wier (2008) use the one-dimensional scale to investigate senior-level business students' professional commitment. Yetmar and Eastman (2000) use the one-dimensional scale to investigate tax practitioners' professional commitment.…”
Section: Measuring Professional Commitmentmentioning
confidence: 99%